Relatório de estágio técnico profissional supervisionado em medicina veterinária: clínica, cirurgia, sanidade e reprodução de bovinos leiteiros - Basso, Larissa Dall’ Agnol (2023)
With the aim of practicing, improving and acquiring new knowledge, the Professional Technical Internship (ETP) is an opportunity to put into practice all the theoretical knowledge acquired during graduation in Veterinary Medicine, in the area intended for professional practice. The ETP was carried out in the city of São Jorge – RS, in the area of ​​Clinic, Surgery, Health and Reproduction of dairy cattle, under the academic guidance of Prof. Jerbeson Hoffmann da Silva, from 07/08/2023 to 03/11/2023 totaling 520 hours. Through the ETP, under local guidance from Veterinary Doctor Josimar Zorzo, it was possible to experience the routine of field care for cattle, carrying out procedures such as clinical examinations, administering medications and assisting in surgical procedures. Regarding reproductive management, gestational diagnoses and reproductive assessments were carried out through palpation and transrectal ultrasound, in addition to fixed-time artificial insemination protocols, pre-synchronization and artificial inseminations. Health management included brucellosis and tuberculosis tests, vaccination for brucellosis, reproductive diseases and deworming. Therefore, this report includes a description of the internship location, a description of the general activities carried out and the conditions monitored during this period, which are divided by etiology. Furthermore, a case of hydrops of the fetal envelope associated with uterine rupture in a Holstein cow will be reported. Finally, the supervised professional technical internship was fundamental for professional and personal maturity, through the opportunity to experience new experiences and challenges in the field. Get to know the routine and the job market, interact with different people, as well as enrich the academic's vision about the future of the profession as a veterinarian.